STRATEGI KOMUNIKASI INTERPERSONAL GURU DALAM MENUMBUHKAN SELF-EFFICACY PESERTA DIDIK SEKOLAH DASAR - Patmawati; Eka Sastrawati; Khoirunnisa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to describe the interpersonal communication strategies used by teachers in growing the self-efficacy of class V students at SD Negeri 139/I Sungai Buluh and to determine the level of students' self-efficacy during science learning. This research was carried out in the even semester of the 2024/2025 academic year. The research method used is qualitative with a phenomenological approach. Research data was collected through observation, interviews, and questionnaires as supporting data in determining students' level of self-efficacy. The strategies that teachers use to grow students' self-efficacy are by creating a pleasant learning atmosphere, holding discussion and question and answer sessions with students, being caring towards students by approaching and providing understanding to students who do not understand the material, motivating and appreciating each student's efforts, giving praise and encouragement to students, creating small discussion groups so that students become more active in learning, creating a class atmosphere where every student feels appreciated and has the same opportunity to participate, teachers also position themselves as friends so that students feel more free to discuss and ask questions. The supporting factors in implementing interpersonal communication strategies in growing students' self-efficacy are class mastery, use of learning media, use of technology, and facilities and infrastructure. Meanwhile, inhibiting factors and obstacles come from internal factors and external factors. Internal factors include students who are not ready to learn and need more attention. Meanwhile, external factors include students who do not bring tools and materials for making media, so it takes longer to find replacement tools and materials. The results of the research show that through the interpersonal communication strategies used by teachers, students are able to grow self-efficacy in science learning. This is shown by the results of the questionnaire that the level of student self-efficacy is in the high category with a result of 47.6%.